Nutlin-3a regulates mouse adipose function by inhibition of CIDEC expression - CHEN Enhui, YANG Jiahui, ZHAO Wei, XIE Xianghong, GUO Yanfang, LIU Xiaojun, YAN Li (Jichu yixue yu linchuang, 2024)
Objective To investigate the effect of Nutlin-3a, a mouse double minute 2 homolog (MDM2) inhibitor, on lipid metabolism of mouse adipose. Methods High-fat diet-induced obesity (DIO) C57BL/6J mice were randomly divided into a control group injected with DMSO and an experimental group injected with Nutlin-3a. Then we conducted glucose tolerance (GTT) and insulin tolerance (ITT) tests. The epididymal white adipose tissue (eWAT), inguinal white adipose tissue (iWAT) and brown adipose tissue (BAT) of animals were isolated and microscopy of WATs with hematoxylin-eosin (HE) staining was performed to observe the morphological changes of adipocytes. The expression of lipid metabolism related gene cell death-inducing DFF45-like effector C (CIDEC) in eWAT were detected by qPCR and Western blot. Results Compared with the control group, Nutlin-3a was found to promote the body weight (P＜0.001),but no effect on glucose tolerance and insulin sensitivity in DIO mice. Nutlin-3a treatment decreased the size of adipocytes and fat deposition in adipose tissue and downregulated the mRNA and protein levels of CIDEC in eWAT. Conclusions Nutlin-3a inhibits the formation of lipid droplets by downregulating expression of CIDEC in white adipose tissue.